(untitled) (Research, Society and Development, 2019)
This article aims to analyze the understanding of teachers of the 4th and 5th grades of Elementary School in relation to the lesson plans elaborated from the thematic units, knowledge objects and skills proposed in the Common National Curricular Base (BNCC) for the area of Nature. This is a qualitative research that develops through a case study, following the principles of Bardin Content Analysis (2010). The data production involved the application of a questionnaire composed of mixed and closed questions and lesson plans prepared by the teachers while participating in a Continuing Education Program. As a result we identify divergences between what teachers claim to contemplate in their planning and what they actually contain, the high rate of use of scientific experiments and the lack of interdisciplinary proposals, as well as the preference for the development of knowledge objects and skills. referred to the thematic unit Matter and Energy to the detriment of the others presented by BNCC.